How to design and evaluate research in education - Fraenkel,Jack R. (McGraw-Hill, 2006)
This text provides a comprehensive introduction to educational research. Each step in the research process is described and discussed in detail, and thorough coverage of the most widely-used research methodologies in education is provided. New to this edition is an expanded focus on qualitative methods. New Parts V and VI provide an expanded introduction to qualitative methods, and take a close look at different qualitative methodologies. Also new is an enhanced chapter on Action Research. Examples of key concepts and ideas in all chapters highlight the texts practicability, and step-by-step analyses of real research studies, and. End-of-chapter Problem Sheets, comprehensive coverage of data analysis, and how to prepare research proposals and reports make the text appropriate both for courses that focus on doing research and for those that stress how to read and understand research. To keep students engaged, the authors' writing is simple and direct. Clarifying examples, summarizing charts, tables and diagrams, numerous illustrations of key concepts and ideas, and a friendly two-color design enhance the content. This is the only copiously illustrated educational research text available. Packaged with the text are an Interactive Student CD-Rom and Student Workbook that provide practice opportunity and resources.